Tidal dynamics in the inter-connected Mediterranean, Marmara, Black and Azov seas. (February 2018) - Ferrarin, Christian; Bellafiore, Debora; Sannino, Gianmaria; Bajo, Marco; Umgiesser, Georg
Highlights: Tides were numerically investigated in the Mediterranean-Marmara-Black-Azov system. The unstructured model SHYFEM was applied to a domain representing the MMBA system. New insights into the tidal exchange between the basins are provided. Along-strait interface slope produces significant fluxes between adjacent basins. Abstract: In this study we investigated the tidal dynamics in a system of inter-connected land-locked basins formed by the Mediterranean, the Marmara, the Black and the Azov seas (MMBA system). Through the application of an unstructured grid hydrodynamic model to a unique domain representing the whole MMBA system, we simulated the tidal propagation and transformation inside each basin and in the straits connecting them. The model performance was evaluated against amplitudes and phases of major tidal constituents from 77 tidal gauges. The numerical results provided a description of the characteristics of the principal semi-diurnal, diurnal and long-term tides over the entire system. Even if the narrow straits act as a barrier for the tidal sea surface oscillations, our numerical results demonstrated that the along-strait interface slope produces water fluxes between the adjacent basins of the same order of magnitude of the climatological transports estimated by several authors. The long-term tidal modulations of the water exchange between the Mediterranean and the Black seas resulted to be non negligible and may partially explain the monthly and fortnightly flow variability observed in the Dardanelles and Bosphorus straits.